2012
DOI: 10.1103/physrevd.85.104002
|View full text |Cite
|
Sign up to set email alerts
|

Nonsingular power-law and assisted inflation in loop quantum cosmology

Abstract: We investigate the dynamics of single and multiple scalar fields with exponential potentials, leading to power-law and assisted inflation, in loop quantum cosmology. Unlike in the classical theory, dynamical trajectories in loop quantum cosmology are generically nonsingular, with a big bounce replacing classical big bang in the Planck regime. Post bounce, after a phase of super-inflation, dynamical trajectories evolve towards the classical attractor in the inflationary scenarios. Depending on the initial condi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 89 publications
1
33
0
Order By: Relevance
“…[18] showed that super-inflation can support enough e-folding number while the Universe contains matter and a small cosmology constant Λ. Also, If one considers the Universe contains a scalar field or multiple scalar field with exponential potentials, the super-inflation is also possible to yield enough e-folding number [16].…”
Section: Horizon Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…[18] showed that super-inflation can support enough e-folding number while the Universe contains matter and a small cosmology constant Λ. Also, If one considers the Universe contains a scalar field or multiple scalar field with exponential potentials, the super-inflation is also possible to yield enough e-folding number [16].…”
Section: Horizon Problemmentioning
confidence: 99%
“…In the standard inflation theory, the scale factor a changes rapidly and the Hubble parameter H remains nearly constant. According to the truth that the e-folding number comes from the changing of the scale factor in standard inflation, someone concluded that the e-folding number created during super-inflation in LQC is not sufficient [14], but then it was found that the e-folding number during super-inflation depends on the initial conditions [19] or the parameter of the potential of the scalar field [16]. To show the change of the scale factor a during the super-inflation stage, we will discuss the Universe filled with the interacting field between massless scalar field and radiation at first, and, then give some numerical results in this section.…”
Section: Scale Factormentioning
confidence: 99%
See 3 more Smart Citations